Phosphorylation of STAT2 on serine-734 negatively regulates the IFN-α-induced antiviral response - Steen, Håkan C. (J Cell Sci, 2016)
Serine phosphorylation of STAT proteins is an important post-translational modification event that, in addition to tyrosine phosphorylation, is required for strong transcriptional activity. However, we recently showed that phosphorylation of STAT2 on S287 induced by type I interferons (IFN-α and IFN-β), evoked the opposite effect. S287-STAT2 phosphorylation inhibited the biological effects of IFN-α. We now report the identification and characterization of S734 on the C-terminal transactivation domain of STAT2 as a new phosphorylation site that can be induced by type I IFNs. IFN-α-induced S734-STAT2 phosphorylation displayed different kinetics to that of tyrosine phosphorylation. S734-STAT2 phosphorylation was dependent on STAT2 tyrosine phosphorylation and JAK1 kinase activity. Mutation of S734-STAT2 to alanine (S734A) enhanced IFN-α-driven antiviral responses compared to those driven by wild-type STAT2. Furthermore, DNA microarray analysis demonstrated that a small subset of type I IFN stimulated genes (ISGs) was induced more by IFNα in cells expressing S734A-STAT2 when compared to wild-type STAT2. Taken together, these studies identify phosphorylation of S734-STAT2 as a new regulatory mechanism that negatively controls the type I IFN-antiviral response by limiting the expression of a select subset of antiviral ISGs.